THE SCHOOL MANAGEMENT AND LEARNER’S QUALITY UNDER RATCHABURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Leelalert , Patsaraporn; Rattanasiraprapha, Nuchnara (Journal of Educational Review Faculty of Education in MCU, 2025)
The purposes of this research were to know 1) the school management under Ratchaburi primary educational Service Area Office 2 2) learner's quality under Ratchaburi primary educational Service Area Office 2 3) the relationship between the school management and learner's quality under Ratchaburi primary educational Service Area Office 2. The simple were 101 schools under Ratchaburi primary educational Service Area Office 2. The research instrument was a questionnaire concerning the school management and learner's quality on Office for National Education Standards and Quality Assessment (Public Organization). The statistical used to analyze the data were frequency, percentage, arithmetic mean, standard deviation and Pearson’s product moment correlation coefficient. The research findings were as follows; 1) The school management under Ratchaburi primary educational Service Area Office 2 were at a high level. 2) Learner's quality under Ratchaburi primary educational Service Area Office 2 were at a high level. 3) There was a relationship between the school management and learner's quality under Ratchaburi primary educational Service Area Office 2 in overall had a middle positive correlation with statistical significance at .01 and correlation coefficient (rxy = 0.659)